Training Motivation at Kolej-Polytech MARA Kuantan - Ahmad Hafizi, Ahmad Giran (2012)
The main purpose of this study is to examine the relationships between self-efficacy, organizational commitment and job involvement with training motivation at Kolej Poly-Tech MARA (KPTM) Kuantan. Survey methodology was used and samples were taken from KPTM Kuantan employees. Data were collected from 120 employees to gather the data. The study showed that there is relationship between self-efficacy and training motivation. Nevertheless, job involvement and organizational commitment do not have a relationship with training motivation at KPTM Kuantan